Number 2 Feibi Recipe Inhibits H2O2-Mediated Oxidative Stress Damage of Alveolar Epithelial Cells by Regulating the Balance of Mitophagy/Apoptosis - Gu, Xiaofeng; Long, Qi; Wei, Wan; Tong, Jiahuan; Li, Zhipeng; Zhang, Zhengju; Jiao, Yang (Frontiers in Pharmacology, 2022)
Reactive oxygen species (ROS)-mediated alveolar epithelial cell (AEC) injury and apoptosis are considered to be the initiating link of idiopathic pulmonary fibrosis (IPF), and protecting AECs can alleviate IPF. This study aimed to explore the protective effect of number 2 Feibi recipe (FBR-2) medicated serum on H2O2-mediated oxidative stress injury in AECs and further explore its mechanism. We found that FBR-2 can regulate downstream antioxidant enzymes expression by activating nuclear factor erythroid 2-related factor 2 (Nrf2), reducing the level of intracellular ROS, protecting mitochondrial function and improving cell survival. FBR-2 can also activate mitophagy through the PINK1/Parkin pathway. Moreover, FBR-2 can inhibit apoptosis by blocking the mitochondrial apoptosis mechanism. In summary, these data indicate that FBR-2 medicated serum can inhibit H2O2-mediated oxidative stress damage in AECs by regulating the balance of mitophagy/apoptosis. This study provides new evidence for the antifibrotic effect of FBR-2 and provides new drug candidates for the clinical treatment of IPF.